Kajian Kepemimpinan, Motivasi Kerja dan Disiplin Kerja Pegawai pada Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Minahasa Selatan. - Tumiwa, Theofilus; Lumolos, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
The purpose of this study is to examine and assess the leadership, motivation and discipline of employees working at the secretariat of the regional parliaments South Minahasa district. This study uses qualitative analysis because the research methods used to examine the condition of natural objects in which the researcher as a key of instrument. By the number of respondents 25 people in the legislature secretariat South Minahasa regency. Primary means of data collection used in qualitative research is by using in-depth interviews addressed to the informants. As for how to capture the informant is using purpose sampling in which employees who are on employees working at the secretariat of the regional parliaments South Minahasa district. Data analysis techniques using data reduction, display data and conclusions. Research results show that applied leadership has not described the influence and example of the lack of leadership. Employee motivations to work become less because there is no direct assessment of the supervisor and the direct assessment of performance of each employee performance. Implementation of labor discipline employees in the secretariat of the parliament is still lacking a sense of responsibility and self-awareness of employees. From the research it can be concluded that the leadership of the secretariat of the South Minahasa regency has not applied the maximum, The motivation is less effective because not all employees are highly motivated to achieve the performance of employees, labor discipline in Minahasa regency secretariat is not implemented with full responsibility. Suggestions in order to support the improvement of leadership has to start from the leader as a role model for employees so that, Â providers can work together with each other mutual support among employees. Work motivation is a necessity that is owned by the employee because it becomes the driving task. Labor disipline employees must have a sense of responsibility and awareness of the regulations should be increased again and confirmed by the rules of labor discipline employees. Keywords: leadership, motivation and discipline of employees working